PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS ANGGOTA KUD PLONGKOWATI TIMUR GODONG - Mutiara Adelina, 09.05.51.0028 (Students Journal of Economic and Management, 2013)
This study is intended to analyze the effect of service quality on satisfaction and loyalty of members of KUD Plongkowati Timur Godong. The object of this research is KUD Plongkowati Timur members. Determination of the sample using purposive sampling method. the data processing using the application SPSS. The method of data analysis using the validity and reliability. Further analysis using multiple linear regression research and testing mediation to explain the relationship between variables. There are three result of the multiple linear regression. First, service quality has positive and significant impact on satisfaction. It can be seen from the result of the regression coefficient service quality is positive (0,765) with significant 0,000 <0,05. It mean that if the service quality better will increase satisfaction. Second, service quality has positive and significant impact on loyalty. It can be seen from the result of the regression coefficient service quality is positive (0,331) with significant 0,000 <0,05. It mean that if the service quality better will increase loyalty. Third, satisfaction has positive and significant impact on loyalty. It can be seen from the result of the regression coefficient satisfaction is positive (0,539) with significant 0,000 <0,05. It mean that if the satisfaction better will increase loyalty.Keywords: service quality, satisfaction, loyalty